Corticospinal modulation induced by sounds depends on action preparedness - Marinovic, Welber; Tresilian, J.; de Rugy, A.; Sidhu, S.; Riek, S. (Wiley-Blackwell Publishing Ltd., 2014)
A loud acoustic stimulus (LAS) presented during movement preparation can induce an early release of the prepared action. Because loud sound has been found to have an inhibitory effect on motor cortex excitability, it is possible that the motor cortex plays little role in the early release of prepared responses. We sought to shed new light on this suggestion by probing changes in corticospinal excitability after LAS presentation during preparation for an anticipatory action. Unexpectedly, we show that the changes in corticospinal excitability after LAS presentation are not fixed. Based on the magnitude of motor-evoked potentials elicited by transcranial magnetic and electric stimulation of the motor cortex, we demonstrate that the effects of auditory stimuli on corticospinal excitability depend on the level of readiness for action: inhibition in early preparation and facilitation close to movement onset. We also show that auditory stimuli can regulate intracortical excitability by increasing intracortical facilitation and reducing short-interval intracortical inhibition. Together, these findings indicate that, at least in part, the early release of motor responses by auditory stimuli involves the motor cortex. © 2013 The Physiological Society.